Chinese Outbound Travel Market – An Analysis of Chinese Tourist Behaviour in the United Kingdom - Wang, Ting (2010)
ABSTRACT The study on consumer behaviour is popular among all industries, and there is no exception for the tourism industry. Actually, a comprehensive understanding of tourist behaviours enables the destination marketers and tour operators to exert effective influences on the customers’ pre-purchase, purchase and post-purchase phases,and further promote the destination as a whole. Chinese outbound tourism industry has a great potential to develop, and grasping this origin market has a great significance for every destination. As the case of UK, it was a relatively new destination for Chinese leisure tourists, and few researches have been conducted on this area. Accordingly, detailed literature reviews on the Chinese outbound tourism market, as well as empirical studies on their behavioural characteristics are thought to be useful for overseas destinations, especially the UK. With a purpose to explore the potential of Chinese outbound travel market, as well as identify their behavioural characteristics in UK, this research utilised both secondary and primary data, and quantitative and qualitative researches are employed together. From a practical perspective, this research contributes overseas destinations in understanding, targeting and marketing the Chinese outbound tourism market. It is hoped that after this research, the value of this market will be noted by destinations, and more effective marketing strategies as well as suitable services will be presented.